Evaluation of psychosocial risks affecting academician using the Sine Trigonometric Pythagorean Fuzzy (ST-PFN) DEMATEL method. - Tepe, Serap; Çabuk, Ahmet; Eti, Serkan; Mertoğlu, Bülent (Work, 2025)
BACKGROUND: In the realm of academia, psychosocial risk factors play a pivotal role, exerting considerable influence on the well-being and performance of scholars. Factors such as excessive workloads, unrelenting performance expectations, time constraints, and competitive atmospheres can detrimentally affect their health and overall quality of life. Moreover, issues like social isolation, work-life imbalance, and academic anxiety further compound these challenges, impeding academic progress and success. OBJECTIVE: Thus, it is imperative to identify, mitigate, and manage psychosocial risk factors effectively to foster a conducive academic environment conducive to productivity and achievement. METHODS: This study employs a novel approach, integrating expert opinions and utilizing sine trigonometry Pythagorean fuzzy numbers to ascertain the degrees of importance and rank psychosocial risk factors through the DEMATEL method. This methodology presents a unique contribution to existing literature, offering fresh insights into this critical area of study. RESULTS: Evaluation of 25 factors reveals burnout, job dissatisfaction, precarious working conditions, lack of trust, unfair treatment, job insecurity, and limited developmental opportunities as primary concerns, underscoring the multifaceted nature of these challenges. CONCLUSIONS: In the occupational sphere, active participation from all stakeholders in addressing psychosocial risks is paramount for effective problem resolution. It is incumbent upon parties involved to discharge their duties, foster collaboration, enhance working conditions, ensure equity, and facilitate avenues for professional growth. Each identified risk factor addressed and preempted translates into a tangible reduction in workplace accidents and occupational ailments, underscoring the tangible benefits of proactive risk management.